CPP-ACP complexe as an alternative to treatment of incisor molar hypomineralization: case report - Micaela CARDOSO1; Kelly Maria Silva MOREIRA1; Andréia Alves CARDOSO1; Regina Maria Puppin RONTANI1 (Faculdade São Leopoldo Mandic, 2019)
The objective of this study was to report the clinical treatment of a child with Incisor Molar Hipomineralization. A 5-year-old Brazilian child, male gender, was diagnosed with Molar Incisor Hypomineralization, reporting high teeth sensitivity. After anamnesis and clinical examination, treatment was conducted with three weekly applications of fluoride varnish containing 5% CPP-ACP complex. Also, it was advice to the patient for using a toothpaste containing fluoride and CPP-ACP (MI Paste Plus). After that, molars with great tooth structure loss were restored with resin modified glass ionomer cement. Prior to the first topical application of varnish with CPP-ACP and fluoride toothpaste containing CPP-ACP, a sensitivity test was conducted using thermal stimulus and facial pain scale. It was observed relative sensitivity decrease between sessions, reporting no sensitivity at the last session before the restoration. The treatment of Molar Incisor Hypomineralization teeth with CPP-ACP complex associated with fluoride varnish can be an alternative to reduce sensivity.